The Basic Requirements For Implementing Six Sigma and its Impact on Creating Smart Organizations: An Analytical Study in Private Universities in The Middle Euphrates Region - Mustafa Hamid Abd Nour; Aseel Ali Mezher (Research Parks Publishers, 2026)
The current research aims to identify the basic requirements for implementing Six Sigma (continuous improvement, teamwork, and fact-based decision-making), and its impact on smart organizations across its dimensions (understanding the environment, continuing education, and strategic vision). The study problem was represented by a number of questions aimed at identifying the intellectual frameworks of its variables, and then diagnosing the level of interest in them in the field, as well as identifying appropriate measures by the organization. Two main hypotheses were developed, from which several hypotheses branched out to measure the level of correlation and influence by analyzing the relationship between these variables. Private universities in the Middle Euphrates region were selected for the field study and testing its hypotheses. A questionnaire was adopted as the primary tool for collecting data related to the field aspect of the study. The sample size reached (168) instructors at the universities under study. A set of results was reached, the most important of which is that the availability of the basic requirements for implementing Six Sigma, such as leadership support, adopting a culture of quality, and the availability of accurate data, is an essential condition for the success of any initiative towards building smart organizations.